Pretibial Edema Is One of the Sign of Thyrotoxicosis A Case of Thyroid Heart Disease and Unilateral Pretibial Edema - Januar Wibawa Martha (The Indonesian Heart Association, 2007)
Thyroid heart disease is one of the many and frequent complication of thyrotoxicosis, which also manifest in extra cardiovascular system. Opthalmopathy is a well-known and well-studied complication of thyro-toxicosis, and another is dermopathy, which manifests as pretibial edema.This case presentation describes a patient of long standing thyrotoxicosis with thyroid heart disease. In this particular case, the patient developed unilateral pretibial edema which posed a diagnostic challenge.In dealing with that, it would be important to con-sider several differential diagnosis. Some of the differ-ential diagnosis of unilateral pretibial edema are actu-ally not proven due to limited hospital stay, but an analysis of differential diagnosis will be presented and hopefully will lead to better recognition of clinical symptoms and signs of thyrotoxicosis, its complica-tions and lead to appropriate diagnostic studies.